(untitled) (The Research of Medical Science Review, 2025)
The current research was aimed to explore the psychological and social factors that are predisposing in onset of delusions in patients with schizophrenia. Qualitative research design was used and thematic analysis was used to taken the themes out of the interviews conducted with patients with schizophrenia. Sample of 10 patients was taken from different mental health rehabilitation centers and hospitals. 5 men and 5 women took part in this research. Before that, verbal informed consent was taken from the patients. Interviews were written on paper with pencil and not recorded in audio or video form. The result of the study claimed different psychological and social factors as loss and death of loved ones, betrayal, physical abuse, unemployment, breakup, and divorce and sibling’s rivalry served as predisposing factors of delusions in patients with schizophrenia. However, these results are not able to be generalized on a larger population because of small sample size and individual differences. Besides, results of the study would be helpful in future for the understanding and counseling of patients with schizophrenia and their families.